Ethical Considerations for a better Collaboration between Architects and Structural Engineers- Design of Buildings with Reinforced Concrete Frame Systems in Earthquake Zones - Hurol, Yonca (Springer Publishing, 2013)
Architects design building structures, although structural design is the profession of structural engineers. Thus, it is better for architects and structural engineers to collaborate starting from the initial phases of the architectural design. However, this is not very common because of the contradictory design processes and value systems held within the two professions. This article provides a platform upon which architects and structural engineers can resolve the value conflicts between them by analysing phases of the structural design of reinforced concrete frame systems in architecture, the criteria of the structural design for each phase and determining the conflicting values for each criterion. The results shown in the article demonstrate that the architectural design of structures is a complex process, which is based on contradictory values and value systems. Finally, the article suggests to architects and structural engineers to use Value Sensitive Design and to choose an appropriate team leader in order to resolve the unethical conflict between them and to avoid any unreasonable decision making.
This article argues that the lack of collaboration between architects and structural engineers during the design of buildings with frame systems causes ethical problems.
Keywords: frame system, collaboration, ethics